2016
DOI: 10.1021/acs.orglett.6b01946
|View full text |Cite
|
Sign up to set email alerts
|

Free-Radical Triggered Ordered Domino Reaction: An Approach to C–C Bond Formation via Selective Functionalization of α-Hydroxyl-(sp3)C–H in Fluorinated Alcohols

Abstract: A free-radical mediated highly ordered radical addition/cyclization/(sp(3))C-C(sp(3)) formation domino reaction is developed. Three new C-C bonds are formed one by one in a mixed system. Furthermore, it represents the first example of cascade C-C bond formation via selective functionalization of α-hydroxyl-C(sp(3))-H in fluorinated alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…To our knowledge, methyl radical guided HAT has not been previously explored for photocatalytic C(sp 3 )–H functionalization 65 , 66 . As such, we set out to understand the reactivity and selectivity effects inherent to the system.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, methyl radical guided HAT has not been previously explored for photocatalytic C(sp 3 )–H functionalization 65 , 66 . As such, we set out to understand the reactivity and selectivity effects inherent to the system.…”
Section: Resultsmentioning
confidence: 99%
“…One elegant resolution is hydrogen-atom-transfer (HAT) via a free-radical process since the bond dissociation energy (BDE) of the (α-OH)­C–H in fluorinated alcohol is comparable to that in general alcohol (BDE TFE = 92.5 kcal/mol; BDE ethanol = 91.5 kcal/mol) . Recently, Liu et al reported the first practical dehydrogenative hydroxyfluoroalkylation of heteroarene with polyfluorinated alcohol via a two-step HAT process (Scheme b) . Nevertheless, electron-deficient molecules are not compatible with this system since the active intermediate could not remain as the (α-OH)­C-centered radical under those conditions.…”
mentioning
confidence: 99%
“…In 2014, Liu reported the reaction of alcohol molecules and isocyanide, and various alkyl-substituted phenanthridines were achieved. 9 …”
mentioning
confidence: 99%